A new carbon additive compounded Li3V1.97Zn0.05(PO4)3/C cathode for plug-in hybrid electric vehicles. (10th July 2015) - Wang, Wenhui; Zhang, Jiaolong; Lin, Yue; Ding, Fei; Chen, Zhenyu; Dai, Changsong
Abstract: The application of lithium ion batteries in plug-in hybrid electric vehicles (PHEVs) requires safety, high energy density, high power density, excellent cyclability and good low temperature performance. On the basis of thermally stable Li3 V2 (PO4 )3 /C and cost-effective performance carbon additives, we designed a Li3 V1.97 Zn0.05 (PO4 )3 /(C+10PB) (PB stands for performance carbon additives PBX101) cathode that meets the above requirements for PHEVs battery. Firstly, its Ragone plot presents an excellent energy density retention at high power rates; secondly, the excellent capacity retention and high Coulombic efficiency of Li3 V1.97 Zn0.05 (PO4 )3 /(C+10PB)-Li half-cell clearly indicates a potential good cyclability of full cells based on Li3 V1.97 Zn0.05 (PO4 )3 /(C+10PB) cathode. Finally, we believe the good low temperature performance of Li3 V1.97 Zn0.05 (PO4 )3 /(C+10PB) ( i.e. retains 91.6% and 76.3% of its capacity at ∼25 °C, when cycled at 0 and -15 °C) is also beneficial to its application in PHEVs.